Where's the Policy? Immigration to New Brunswick, 1945-1971 - Steel, Heather (Acadiensis, 2006)
Abstract This article examines the role of immigration in New Brunswick's public policy between 1945 and 1971. While the New Brunswick government put considerable energy and money into attracting immigrants between 1867 and 1930, these efforts ceased during the Depression and have only recently been revived. Concerned with high levels of out-migration and unemployment, politicians and economic planners under three premiers in the post-war period (John McNair, Hugh John Flemming and Louis J. Robichaud) promoted a "New Brunswick first" policy, arguing that incentives for immigrants would give them benefits that native-born citizens did not enjoy. This approach contrasts sharply with immigration policy in other have-not provinces such as Manitoba, where concerns were being raised that federal immigration policy was ineffective in addressing regional needs. As this article suggests, research on provincial immigration programmes offers valuable insights not only on the regional dimensions of Canada's immigration policy but also on regional political cultures.